The Contributions of Nawawi al-Bantani In the Development of National Law of Indonesia - Sanusi, Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2018)
This study examines the thoughts of Sheikh Nawawi al-Bantani, a great Banten scholar who lived in 1813-1897 AD. The aim is to find out about his thoughts on several legal issues, especially those related to family law. This study is fully literary using the content analysis method as an analytical tool. This study concluded that Sheikh Nawawi al-Bantani tended to follow the Shafi’i school. This can be seen from his thoughts when discussing family law issues, ranging from marriage contracts, marriage conditions, guardians and witnesses, to divorce problems and its legal consequences. When discussing the position and role of a husband in a household, al-Bantani stressed that a husband is a leader in his household. He is obliged to fulfill all the needs of his wife and children, especially those related to food, clothing, residence, education and other needs. Al-Bantani’s thoughts were subsequently adopted into positive law in Indonesia, especially in Law No. 1/1974 concerning marriage and Compilation of Islamic Law (KHI), which become his biggest contribution in the development of National Law.